Argonaute protein-based nucleic acid detection technology - Wu, Zhiyun; Yu, Li; Shi, Weifeng; Ma, Jinhong (Frontiers in Microbiology, 2023)
It is vital to diagnose pathogens quickly and effectively in the research and treatment of disease. Argonaute (Ago) proteins are recently discovered nucleases with nucleic acid shearing activity that exhibit specific recognition properties beyond CRISPR -Cas nucleases, which are highly researched but restricted PAM sequence recognition. Therefore, research on Ago protein-mediated nucleic acid detection technology has attracted significant attention from researchers in recent years. Using Ago proteins in developing nucleic acid detection platforms can enable efficient, convenient, and rapid nucleic acid detection and pathogen diagnosis, which is of great importance for human life and health and technological development. In this article, we introduce the structure and function of Argonaute proteins and discuss the latest advances in their use in nucleic acid detection.